Comparison Study of Some Hematological and Biochemical Blood Characteristics Between Domestic and Barn Chickens - Asem Ramadan Amar Mohamed; Abdul hakim Khalefah Alour; Farag Elmhdi Jabreil (African Journal of Advanced Pure and Applied Sciences, 2023)
This work was carried out at the Faculty of Veterinary Medicine and Agriculture, University of Zawia, in November 2022, to a comparison of hematological and biochemical blood characteristics between domestic and barn chickens. Blood was collected from the wing vein of 20 chickens and divided into two parts. The first part was for blood hematology and the second one for biochemical analysis. The results showed there were no significant differences in the values of RBC, HB, and PLT, the significant differences in PCV were the group of domestic chickens, recorded the highest percentage of 37.36, while the control group 35.1. There was a significant increase in WBC, and the group of domestic chickens recorded the best value (25,36) followed by the control group, which recorded (25,28). Total lipids showed no significant differences in the values of T. Lipid and Triglyceride. Cholesterol, in the group of barn chickens, recorded the highest significant difference 150, 6 on the group of domestic chickens, which recorded106, 4, while the domestic chickens recorded the highest significant difference in HDL values compared to the control group, where it recorded 82, 76,2 respectively. The total protein in the control group recorded a slightly significant difference compared to the group of domestic chickens, as it recorded 5.98, while the other group recorded 5.3. Albumin in the group of domestic chickens was recorded at 2.28 and in the control group at 1.84. In the group of barn chickens, Globulin recorded 1,472 while in the other group recorded 3.64, respectively.